ANALISIS VEGETASI DAN JENIS VEGETASI DOMINAN YANG BERASOSIASI DENGAN MANGGARSIH (Paramerian laevigata) DI KAWASAN PEGUNUNGAN MERATUS, KALIMANTAN SELATAN - Wira Amirina; Yudi Firmanul Arifin; Eva Prihatiningtyas (Universitas Lambung Mangkurat, 2020)
The Meratus Mountains have tremendeous of biodiversity that usefull as a medicinal plant. One of the medicinal plants is manggarsih. Manggarsih is often used by Dayak Meratus women as raw material for herbal medicine which is efficacious herbs to protect female sex organs. However, these plants have begun to decline in their habitat while harvesting only relies on their natural habitat. Therefore, it is important to do research on the dominant inter-vegetation association which aims to analyze the composition and structure of vegetation and any dominant types that have an association relationship with manggarsih so that later can be used as consideration for ex situ conservation. This study used a purposive sampling method for determining sample points, vegetation analysis using Important Value Indeks (IVI) and continued with the Ochiai Index to analyze plant associations. The results found that there were 36 types of vegetation in the community unit, 19 species of seedlings, 21 species of seedlings, 7 pillars and 6 species of trees. The manggarsih plant association with 5 dominant which has a very strong relationship occurs with the type of mahang for seedling and sapling levels while at the pole level and tree the strong association occurs with the type of rubber.Keyword: Analysis of vegetation, association, manggarsih